Changing self‐control: Promising efforts and a way forward. Issue 173 (7th October 2020) - Piquero, Alex R.; Rocque, Michael
Abstract: Researchers have long known that self‐control, or impulse control, is important for a variety of life outcomes, including health, education, and behavior. In criminology, the most popular perspective on self‐control argues that it is a multidimensional trait that is relatively stable after about age 8. Some work, however, has shown that in fact, self‐control may not be as stable as originally thought. This article examines the evidence on interventions seeking to enhance self‐control and subsequently to reduce delinquent or criminal behavior. The evidence is growing but still in need of development. Implications for future research and practice are discussed in the conclusion.